Microbial quorum quenching activities in marine water, wetland water, and rainforest soil / Wong Cheng Siang - Wong , Cheng Siang (2010)
Quorum sensing refers to the bacterial cell-to-cell communication phenomenon that is employed to regulate a wide range of activities in a variety of bacteria. One of the most extensively studied mechanisms is that of Gram-negative bacteria utilizing N-acyl homoserine lactone as the signaling molecule. Quorum quenching on the other hand refers to the interference of quorum sensing, that can be achieved by, inter alia, directly inactivating the signaling molecule, and thus preventing the expression of certain genes, notably those regulating virulence. This study aimed to isolate N-acyl homoserine lactone-degrading microorganisms from Malaysian marine water, wetland water, and rainforest soil using a defined enrichment medium. The present work successfully yielded three bacterial strains and one fungal strain from three environmental samples. The major finding generated by this study was the characterization of a basidiomycetous yeast strain isolated from wetland water, which was capable of degrading a variety of N-acyl homoserine lactones and growing on 3-oxo-C6-HSL. To the best of our knowledge, this is the first report of such activities in the fungal strain Trichosporon. The N-acyl homoserine lactone-degrading bacterial strains include Bacillus cereus isolated from rainforest soil and two Pseudomonas aeruginosa strains isolated from marine water. Bacillus cereus strain KM1S was able to degrade rapidly 3-oxo-C6- HSL and 3-oxo-C8-HSL in vitro. The kinetic of the AHL turnover was characterized using RRLC. The aiiA homologue in this isolate was found to contain the motif 106HXDH-59 amino acids-H169-21 amino acids-D191, essentially needed for the AHL degradation activity. The AHL degrading activities were confirmed in the marine pseudomonads using RRLC and the quorum quenching homologue genes quiP and pvdQ were successfully PCR amplified.